Karakter Meristik dan Morfometrik Spesies Ikan Asing Invasif Parachromis managuensis (Günther 1867) di Waduk Penjalin, Brebes, Jawa Tengah - Adinda Kurnia Putri; Lilik Kartika Sari; Muslih Muslih; Nabela Fikriyya; Ani Haryati (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
The Jaguar Guapote, Parachromis managuensis is an alien species from the Cichlids that are potentially invasive and threaten the native and endemic fish species resources in Penjalin Reservoir, Brebes, Central Java.  This research aims to identify the Jaguar Guapote fish according to its morphometric and meristic characteristics. 50 Jaguar Guapote fish were collected from the fisherman around Penjalin Reservoirs and analyzed 20 morphometric and seven meristic characteristics. Twenty-one fish were in the juvenile stage while the rest 29 were in an adult stage that could be distributed into seven length classes. One-way ANOVA, Cluster Analysis, and Principal Component Analysis were performed to test the differences of morphometric characters, while the Kruskal-Wallis test was used to analyze the difference of its meristic characters according to length classes. The result of One-Way ANOVA shows significant differences in 15 morphometric characters. The smaller and the larger fish can differentiate by their head morphologies such as PoL (Post Orbital Length), SnL (Snout Length), HL (Head Length), dan PreDL (Pre-Dorsal Length). Although, the meristic characters revealed no significant differences based on the length classes.